To Accept One’s Fate or Be Its Master: Culture, Control, and Workplace Choice - Eisen, Charis; Ishii, Keiko; Miyamoto, Yuri; Ma, Xiaoming; Hitokoto, Hidefumi (Frontiers in Psychology, 2016)
Utilizing three student (Study 1) and non-student samples (Study 2), we examined cultural differences in workplace choice for North Americans, Germans, and Japanese. We focused on the desire for control as a potential mediator (i.e., the underlying mechanism) to explain cultural differences in this important life decision. Given culturally divergent embodiments of independent vs. interdependent models of agency, we expected and found that, compared to North Americans and Germans, Japanese were more likely to prefer a workplace with a payment system that maintains social order rather than one that rewards individual achievement. Furthermore, we found that Japanese tend to give greater consideration to family opinions in their choice of workplace. As predicted, desire for control (i.e., the motivation to have control over various events) was stronger for North Americans and Germans than Japanese, and explained cultural differences in choice of workplace.